The Development of Islam During The Al-Ayyubiyah Dynasty In 567-648 H / 1171-1250 M - Desriadi, Desriadi (Islamic Family Law Department, Sharia Faculty, Stai Syekh Abdur Rauf, Aceh Singkil, 2024)
The Al-Ayyubiyah dynasty was a dynasty after the Fathimiyyah dynasty which had a Sunni sect with the first sultan Shalahudin Yusuf Al-Ayyubi, a Kurdish tribe from Azerbaijan who migrated to Iraq. His father was Najmuddin Bin Ayyub, a governor of Tikrit who moved to Mushol then to Damascus. Najmuddin and his brother Asadudin Shirkuh became commanders of Mahmud Zanki, the ruler of Seluk, in Syria at that time. It has been mentioned above that the last ruler of the Fatimid dynasty was Al-Adhid who succeeded the previous caliph. When Al-Adhid became caliph, a very cruel incident occurred, namely when Al-Qais became vizier at that time, Ibn Raziq, Al-Adhid murdered Ibn Raziq and not long afterward Sawar succeeded in replacing the new vizier. This incident could cause jealousy from other parties, at that time Dhirgam was also aiming for the position of vizier too, with his full strategy Dhirgam succeeded in defeating Sawar so that Sawar was forced to flee to Syria